Inter-methodological quantification of the target change for performance test outcomes relevant to elite female soccer players. Issue 2 (3rd April 2022) - Datson, Naomi; Lolli, Lorenzo; Drust, Barry; Atkinson, Greg; Weston, Matthew; Gregson, Warren
ABSTRACT: Introduction: Valid and informed interpretations of changes in physical performance test data are important within athletic development programmes. At present, there is a lack of consensus regarding a suitable method for deeming whether a change in physical performance is practically relevant or not. Methods: We compared true population variance in mean test scores between those derived from evidence synthesis of observational studies to those derived from practioner opinion (n = 30), and to those derived from a measurement error (minimal detectable change) quantification (n = 140). All these methods can help to obtain 'target' change score values for performance variables. Results: We found that the conventional 'blanket' target change of 0.2 (between-subjects SD) systematically underestimated practically relevant and more informed changes derived for 5-m sprinting, 30-m sprinting, CMJ, and Yo-Yo Intermittent Recovery Level 1 (IR1) tests in elite female soccer players. Conclusions: For the first time in the field of sport and exercise sciences, we have illustrated the use of a principled approach for comparing different methods for the definition of changes in physical performance test variables that are practically relevant. Our between-method comparison approach provides preliminary guidance for arriving at target change values that may be useful for research purposes and tracking of individual female soccer player's physical performance.